Crystal and supramolecular structures of dysprosium(III) 2-methoxybenzoate tetrahydrate - Siqueira, Adriano B. [UNESP]; Legendre, Alexandre de O. [UNESP]; Ellena, Javier A.; Mauro, Antonio Eduardo [UNESP]; Ionashiro, Massao [UNESP] (My University, 2008)
The compound dysprosium(III) 2-metoxybenzoate, {[Dy(2-MeO-Bz)2μ-(2-MeO-Bz)(H2O)2]2·4H2O}n (2-MeO-Bz = 2- methoxybenzoate), was synthesized from a reaction mixture containing DyCl3 and Na(2-MeO-Bz), and characterized by single-crystal X-ray diffraction. The molecular structure showed dinuclear units in which each Dy(III) ion is coordinated by nine oxygen atoms. The carboxylato groups are bound to the dysprosium centers in two modes: bidentate chelating and tridentate chelating-bridging. Besides this, the occurrence of hydrogen bonds involving a coordinated water molecule and carboxylato groups leads to the formation of helicoidal chains along the crystal lattice, resulting in a supramolecular one-dimensional polymer. 2008 © The Japan Society for Analytical Chemistry.